An etymological study of Singapore sign language : the influence of American sign language on Singapore sign language - Lee, Naomi Elizabeth (2016)
Though there is no officially recognized national sign language in Singapore, Singapore Sign Language (SgSL) is recognized by the local deaf community. It has influences from Shanghainese Sign Language (SSL) and American Sign Language (ASL), and is continually developing with locally generated signs. This study aims to give an insight into the influence of ASL on SgSL, which serves as a first look into the etymology of SgSL. 14 participants were recruited in this study; 3 participants were given a Swadesh list for sign languages consisting of 100 words, which they were asked to sign in SgSL. The videos of ASL signs for the same words were obtained online and presented alongside the SgSL signs to the other 11 participants, who gave judgments about the similarities of each pair of signs. The signs were also transcribed using the Hamburg Sign Language Notation System, or HamNoSys, and further analyzed based on handedness and four traditional phonological parameters – handshape, location, movement and orientation. This was done by calculating the Levenshtein distances between each pair of transcriptions. The similarity of the signs was then determined after consideration of the participants’ judgments and the analysis of phonological parameters, and it was found that the signs were similar to a great extent, which suggests that SgSL is heavily influenced by ASL